2006
DOI: 10.1523/jneurosci.2905-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Precise Spatial Relationships between Mossy Fibers and Climbing Fibers in Rat Cerebellar Cortical Zones

Abstract: Classically, mossy fiber and climbing fiber terminals are regarded as having very different spatial distributions in the cerebellar cortex. However, previous anatomical studies have not studied these two major cerebellar inputs with sufficient resolution to confirm this assumption. Here, we examine the detailed pattern of collateralization of both types of cerebellar afferent using small injections of the bidirectional tracer cholera toxin b subunit into the posterior cerebellum. The cortical and zonal locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
133
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 45 publications
9
133
2
Order By: Relevance
“…After electrical stimulation of the LRN, Xu and Edgley (2010) observed latencies of excitatory responses ranging from 14.1 to 23.6 ms in 4 out of 27 GoCs. However, in Crus II, projections from pontine nuclei outnumber those from the LRN (Pijpers et al 2006;Wu et al 1999).…”
Section: Origins Of Response Latenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…After electrical stimulation of the LRN, Xu and Edgley (2010) observed latencies of excitatory responses ranging from 14.1 to 23.6 ms in 4 out of 27 GoCs. However, in Crus II, projections from pontine nuclei outnumber those from the LRN (Pijpers et al 2006;Wu et al 1999).…”
Section: Origins Of Response Latenciesmentioning
confidence: 99%
“…Mossy fibers originating in the trigeminal nuclei, basal pontine nuclei, and nucleus reticularis tegmenti pontis bifurcate to make multiple projections to Crus IIa, forming discontinuous patches or stripes (Pijpers et al 2006;Serapide et al 2002;Woolston et al 1981), colocalized with climbing-fiber projections of similar body representations (Sugihara and Shinoda 2004). Vos et al (2000) described four response patterns in GoCs occurring with almost equal frequency.…”
Section: Origins Of Response Variationmentioning
confidence: 99%
“…Even finer longitudinal compartmentalization in the cerebellar cortex is possible based on the expression pattern of aldolase C (zebrin II) (Hawkes and Leclerc, 1987). Recently, several groups have demonstrated a correspondence between the olivocortical projection pattern and aldolase C compartments of the cerebellar cortex (Voogd et al, 2003;Voogd and Ruigrok, 2004;Pijpers et al, 2005Pijpers et al, , 2006. This suggests that molecular expression, olivocortical topography, and functional compartmentalization are integrated within the organization of the cerebellar cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The granular layer is also subdivided into stripes (for review, see Ozol and Hawkes, 1997) that also align with the overlying Purkinje cell compartments [e.g., mossy fiber terminal fields (Matsushita et al, 1991;Akintunde and Eisenman, 1994;Ji and Hawkes, 1994;Voogd et al, 2003;Pijpers et al, 2006)], and an elaborate mosaic of patches is revealed both in tactile receptive field maps (Welker, 1987) and by histological treatments (Hawkes et al, , 1998. Finally, functional studies have also demonstrated parasagittal stripes in the cerebellum Larson, 1973, 1980) (for review, see Voogd et al, 1996) with direct correlations with particular Purkinje cell stripes (Chockkan and Hawkes, 1994;Chen et al, 1996;Hallem et al, 1999).…”
Section: Introductionmentioning
confidence: 99%